Four-Year Outcome of Aflibercept Treatment-Naïve Patients for Neovascular Age-Related Macular Degeneration: Evidence from a Clinical Setting - Yanel Gayadine-Harricham; Virginie Rufin; Sandrine Law-Koune; Thi Ha Chau Tran (Journal of Ophthalmology)
Introduction. The objective of the study is to report 4-year treatment outcome with intravitreal Aflibercept injections for neovascular age-related macular degeneration (nAMD) as first life therapy in real-life. Patients and Methods. This is a prospective, monocenter, observational case series analysis. Data from treatment-naïve patients with nAMD with at least 4 years of follow-up were included in the analysis. Data including age, gender, and visual acuity measured on Early Treatment of Diabetic Retinopathy Study charts (ETDRS) and injection numbers were recorded. Spectral domain optical coherence tomography (SD-OCT) data at baseline, month 3, month 6, month 12, year 2, 3, and 4 were also recorded. Patients were treated with a modified treat and extend (T&E) regimen. Results. Of the 48 eyes with nAMD treated, only 31 eyes were available at the 4-year follow-up. The mean age was 81 ± 8 years. The VA gain was 7.3 ± 12.7 letters at 1 year 6.5 ± 12.5 letters at 2 years, VA gain 5.2 ± 17 letters at 3 years, and 6.2 ± 18.6 letters at 4 years. The reduction of central retinal thickness was 118 ± 187 μm at 4 years. Complete resolution of fluid was obtained in 18/31 eyes. The total number of injections was 5.7 ± 2.0 during the first year, 2.9 ± 2.9 during the second year, 3.5 ± 3.3 during the third year, and 4.0 ± 3.4 during the fourth year. The total number of injections was 16 ± 10.6, ranging from 3 to 52 injections. Ten eyes developed macular atrophy over the 4-year period. Conclusion. The results suggest that good long-term morphological and functional outcome can be achieved using Aflibercept in clinical setting.